Improving Skills in Making Plastic Canvas Bags Through the Direct Instruction Learning Model for Deaf Children - Deska Dwi Rahma Anggraini; Zulmiyetri Zulmiyetri; Mega Iswari; Asep Ahmad Sopandi; Riza Elita (Universitas Muhammadiyah Enrekang, 2024)
This research discusses the problems of deaf students who experience difficulties in the skills of making plastic canvas bags. This research aims to determine the process of improving students' skills in making plastic canvas bags through a direct instruction learning model. The type of research is classroom action research in class VIII SLB Negeri 1 Lubuk Basung with a qualitative and quantitative approach. The research procedure consists of planning, action, observation and reflection carried out over two cycles using data collection techniques in the form of observation, documentation and tests. The results obtained are that the ability of deaf students in class VIII SLB Negeri 1 Lubuk Basung in making plastic canvas bags can be improved through the direct instruction learning model.